A synthetic polymeric biolubricant imparts chondroprotection in a rat meniscal tear model. (November 2018) - Wathier, Michel; Lakin, Benjamin A.; Cooper, Benjamin G.; Bansal, Prashant N.; Bendele, Alison M.; Entezari, Vahid; Suzuki, Hideki; Snyder, Brian D.; Grinstaff, Mark W.
Abstract: Intra-articular injection of hyaluronic acid (HA) is used to treat osteoarthritis (OA) as a viscosupplement, yet it only provides short-term benefit because HA is cleaved by hyaluronidase and cleared out of the joint after several days. Therefore, we developed a new polymer biolubricant based on poly-oxanorbornane carboxylate to enhance joint lubrication for a prolonged time. Rheological and biotribological studies of the biolubricant reveal viscoelastic properties and coefficient of friction equivalent and superior to that of healthy synovial fluid, respectively. Furthermore, in an ex vivo bovine cartilage plug model, the biolubricant exhibits superior long-term reduction of friction and wear prevention compared to saline and healthy synovial fluid. ISO 10993 biocompatibility tests demonstrate that the biolubricant polymer is non-toxic. In an in vivo rat medial meniscal tear OA model, where the performance of the leading HA viscosupplement (Synvisc-one ® ) is comparable to the saline control, treatment with the biolubricant affords significant chondroprotection compared to the saline control.